Parkinson’s disease patients show impaired corrective grasp control and eye-hand coupling when reaching to grasp virtual objects - Lukos, Jamie R. (2013)
The effect of Parkinson’s disease on hand-eye coordination and corrective response control during reach-to-grasp tasks remains unclear. Moderately impaired Parkinson’s disease patients (PD, n=9) and age-matched controls (n=12) reached to and grasped a virtual rectangular object, with haptic feedback provided to the thumb and index fingertip by two 3-degree of freedom manipulanda. The object rotated unexpectedly on a minority of trials, requiring subjects to adjust their grasp aperture. On half the trials, visual feedback of finger positions disappeared during the initial phase of the reach, when feedforward mechanisms are known to guide movement. PD patients were tested without (OFF) and with (ON) medication to investigate the effects of dopamine depletion and repletion on eye-hand coordination online corrective response control. We quantified eye-hand coordination by monitoring hand kinematics and eye position during the reach. We hypothesized that if the basal ganglia are important for eye-hand coordination and online corrections to object perturbations, then PD patients tested OFF medication would show reduced eye-hand spans and impoverished arm-hand coordination responses to the perturbation, which would be further exasperated when visual feedback of the hand was removed. Strikingly, PD patients tracked their hands with their gaze, and their movements became destabilized when having to make online corrective responses to object perturbations exhibiting pauses and changes in movement direction. These impairments largely remained even when tested in the ON state, despite significant improvement on the Unified Parkinson’s Disease Rating Scale. Our findings suggest that basal ganglia-cortical loops are essential for mediating eye-hand coordination and adaptive online responses for reach-to-grasp movements, and that restoration of tonic levels of dopamine may not be adequate to remediate this coordinative nature of basal ganglia modulated function.